1997
DOI: 10.1002/etc.5620160513
|View full text |Cite
|
Sign up to set email alerts
|

Differential survival of fathead minnows, Pimephales promelas, as affected by copper exposure, prior population stress, and allozyme genotypes

Abstract: Two populations of fathead minnows (F1, offspring of survivors of an acute fluoranthene exposure; N1, naive hatchery fish born in outdoor ponds) were concurrently exposed to approximately 850 μg/L of copper for 132 h. During the exposure, 49% of the F1 and 85% of the N1 minnows died. A curled operculum deformity, detected in 54% of the F1 population, was significantly related to mortality. A failure time regression model, combining both the F1 and N1 populations together, was fit to examine the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
(33 reference statements)
3
23
0
Order By: Relevance
“…These results indicate differential tolerance of fish genotypes to an acute pesticide stress, as has been documented for a variety of aquatic species subjected to heavy metal contamination [3–12]. Our study allowed a total of eight independent cases in which to examine variability in genotype tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results indicate differential tolerance of fish genotypes to an acute pesticide stress, as has been documented for a variety of aquatic species subjected to heavy metal contamination [3–12]. Our study allowed a total of eight independent cases in which to examine variability in genotype tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to other studies with mosquitofish, which reported that large fish were more tolerant of chlorpyrifos [15] and uranyl nitrate [5] than smaller fish. Similar to our results, two recent studies with the fathead minnow ( Pimephales promelas ) have reported negative associations between fish size and TTD during copper exposure, with larger fish having shorter TTD [11,12]. Unlike our results, however, significant associations occurred between specific genotypes and fish size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences of about an order of magnitude have similarly been found between the three species with exposure to individual organic and inorganic chemicals [23]; however, this is not always the case [24]. Interclonal differences in toxicity test responses have been documented for D. magna [25], genetic differentiation has been documented for laboratory populations of Hyalella azteca [26] and fathead minnows ( Pi‐mephales promelas ) [27], and genetic differences are a major factor affecting fathead minnow survival in toxicity tests [28]. Because of such differences, certainty in the identity of toxicity test species is important.…”
Section: Usefulnessmentioning
confidence: 99%